Why Macro Practice Matters. (2nd July 2016) - Reisch, Michael
ABSTRACT: This article asserts that macro practice is increasingly important in today's rapidly changing and complex practice environment. It briefly explores the history of macro practice in U.S. social work, summarizes its major contributions to the profession and to U.S. society, and provides some suggestions for how social work programs can expand interest in macro practice among their students and increase the number of students who pursue macro-oriented careers.